Mechanistic visco-elastic modeling of shear deformation and failure in internally-reinforced geosynthetic clay liners - Baukus, Aaron, author; Bareither, Christopher A., advisor; Scalia, Joseph, committee member; Yourdkhani, Mostafa, committee member (Colorado State University. Libraries, 2022)
Analysis and prediction of the shear behavior of a non-heat-treated needle punched geosynthetic clay liner (NHT NP GCL) have been conducted using a mechanistic model. A three-element Kelvin-chain model was employed to simulate the incremental loading of a rapid loading shear test. A performance analysis initially was conducted to evaluate variation in model parameters with respect to differences in physical properties of GCLs (i.e., peel strength) and experimental conditions (i.e., normal stress, temperature, creep shear stress). The optimized model parameters demonstrated sensitivity to the variation in internal and external factors and yielded empirical relationships that were carried forward to test model applicability for predicting time-to-failure for an internally-reinforced GCL. These data trends in combination with creep-test data were used to calibrate the creep deformation model. Time-to-failure predictions performed with the calibrated creep deformation model resulted in a percent error < 9%. A modified model-calibration procedure was developed to extend model applicability to stress conditions common in practice. The modified calibration procedure was used to predict NHT NP GCL creep deformation in a hypothetical landfill cover system. The time required for the projected deformation to surpass 3 mm exceeded one million years for all stress conditions evaluated, which suggested that the NHT NP GCL will not experience creep failure in the low-stress cover scenarios evaluated.